1996
DOI: 10.1093/molehr/2.7.527
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects of implantation

Abstract: Several adhesion molecules have been shown to occur at the surface of endometrial cells. One of these is the integrin alpha v subunit which associates with various beta chains including beta 5. We demonstrate the presence of integrin beta 5 polypeptide in human endometrial epithelial cells throughout the menstrual cycle using immunocytochemistry with monospecific antibodies, and at the mRNA level by thermal amplification from endometrial cDNA. Integrin beta 5 is also found in a population of bone marrow-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…These receptor molecules facilitate the preferential entry of WNV and kunjin virus (a subtype of WNV) through the apical surface. Similarly, apical localization of ␣ v and ␤ 3 integrin subunits expression was observed in polarized cells (35). This provided further evidence of the specificity of WNV for ␣ v ␤ 3 integrin.…”
Section: Discussionsupporting
confidence: 62%
“…These receptor molecules facilitate the preferential entry of WNV and kunjin virus (a subtype of WNV) through the apical surface. Similarly, apical localization of ␣ v and ␤ 3 integrin subunits expression was observed in polarized cells (35). This provided further evidence of the specificity of WNV for ␣ v ␤ 3 integrin.…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, chemokines have been implicated in a number of reproductive events, including ovulation, menstruation, embryo implantation, and parturition and disease conditions (i.e., endometriosis and cancer) [36,37]. ITGB5 (integrin beta 5) has also been implicated in cell migration and angiogenesis during embryo implantation due to its apical expression on glandular and luminal epithelial cells [38]. Previous research has demonstrated that the expression of ITGB5 , which regulated by chemokines (such as CX3CL1 and CCL14), could increase trophoblast adherence and migration at the maternal-fetal interface [39].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that the aberrant expression of integrin αvβ3 is associated with infertility and recurrent pregnancy loss (Lessey et al, 1995; Liu et al, 2012). In mice, αvβ3 is expressed in the uterine luminal epithelium and the blastocyst during implantation, and injection of RGD peptides or neutralizing antibody against the αv or β3 subunit into the mouse uterine cavity reduces the rate of implantation compared to injection of BSA or non-RGD peptides, suggesting its participation in mediating the trophectoderm-luminal epithelium interaction (Aplin et al, 1996; Illera et al, 2000; Sutherland et al, 1993). There is evidence that integrin signaling modulates trophoblast adhesion to extracellular matrices via activation of phospholipase C-γ to initiate phosphoinositide signaling and intracellular calcium mobilization during blastocyst implantation (Wang et al, 2002, 2007b).…”
Section: Cell-cell Interactions: the Nature Of Embryo Implantationmentioning
confidence: 99%